Pandangan Fikih Kontemporer Terhadap Akad Nikah Online di Masa Pandemi Covid-19 - Dewi Puruhita Suci; Assyifa Salsabila; Meilinda Salsabila Mawaddah; Nurmala Septi (Indo Publishing, 2025)
The Covid-19 pandemic has had a major influence on various aspects of life, including the implementation of worship and social interactions, one of which is marriage. Physical distancing policies and social policies have led to the emergence of online wedding practices as an alternative. This article aims to examine modern jurisprudence's views on the validity of online marriage during the pandemic using a qualitative approach and literature review. Research findings indicate that primary placements focus on providing pool conditions. The Hanafiyah school, with its emphasis on the unity of time, opens up more opportunities for the validity of online marriages. Meanwhile, the Shafi'iyah School, which requires the unity of place and time, generally declares it invalid. However, in emergency situations such as the pandemic, many contemporary ulama and fatwa institutions, including the results of the ijtima' of the MUI fatwa commission, have begun to consider the validity of the marriage with strict conditions, such as certainty of identity, valid audio-visual witness evidence, and implementation carried out simultaneously.